2021
DOI: 10.7759/cureus.20305
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and the Perceived Impact of Epilepsy in Children and Adolescents in the Eastern Province of the Kingdom of Saudi Arabia

Abstract: Objectives This cross-sectional study aimed to assess the perceived impact of epilepsy on children and adolescents and analyze its aspects. Materials and methods The study included patients with epilepsy aged between and two and 19 years old in three major hospitals in the Eastern Province of Saudi Arabia. Data were collected through an online survey. Results The mean score percentage of the quality of life (QOL) assessment was 65.6. This study showed bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…It has been shown that the underlying cause of SE is a highly important predictor of the outcome after SE; hence, there is a need for high-quality long-term data looking at QoL, neuroimaging, the use of continuous infusions, and the cognitive and behavioral outcomes of children who suffer SE. Similar findings were found in a second questionnaire by Horaib, Wesal, and colleagues [30]. More frequent seizures, the number of fears, concerns, and worries that patients and caregivers had, and prolonged treatment duration all had a negative impact on quality of life, while better family states and being male had a positive impact.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…It has been shown that the underlying cause of SE is a highly important predictor of the outcome after SE; hence, there is a need for high-quality long-term data looking at QoL, neuroimaging, the use of continuous infusions, and the cognitive and behavioral outcomes of children who suffer SE. Similar findings were found in a second questionnaire by Horaib, Wesal, and colleagues [30]. More frequent seizures, the number of fears, concerns, and worries that patients and caregivers had, and prolonged treatment duration all had a negative impact on quality of life, while better family states and being male had a positive impact.…”
Section: Resultssupporting
confidence: 81%
“…(2021) [30] A cross sectional study conducted with Children (aged two to nine) and teenagers (aged 10 to 19) who had been diagnosed with epilepsy and were being monitored in epilepsy clinics were given an online questionnaire. The questionnaires were made to collect data on the following important topics: demographic data, seizure incidence, seizure medication, and length of treatment.…”
Section: Jafarpour Saba Et Al (2019) [29]mentioning
confidence: 99%
See 2 more Smart Citations
“…Quality of life (QoL) depends on numerous factors. In the case of children with epilepsy, some of those factors are directly linked to frequent seizures and adverse effects of the medication taken [ 10 , 11 , 12 , 13 ]. QoL is a complex and multidimensional construct that represents the general well-being of an individual by outlining individual positive and negative aspects of life [ 14 ].…”
Section: Introductionmentioning
confidence: 99%